Losses in weight of cowpea seeds infested by weevil - Oliveira, Francisco José de; Santos, José Higino Ribeiro dos; Alves, José Ferreira; Paiva, José Braga; Assunção, Marcos Vinicius (Pesquisa Agropecuaria Brasileira, 2014)
This investigation was carried out to find a rapid procedure that permits to relate the indexes of infestation by the weevil Collosobruchus maculatus F. (1775) with the percentage of losses of seed weight of cowpea (Vigna unguiculata (L.) Walp). As such, the seeds of the varieties CE-1, CE-2, CE-25, CE-31 and CE-218 were infested with adults of the above mentioned insect pest. The results led to the conclusion that number of tipical holes made by C. maculatus in the samples of 100 seeds of cowpea obtained from the damaged lots could be related to the percentage Posses of seed weight by means of the equation Y = 0.2222 + 0.5042X within the limits of 6.08 to 28.10 holes.